Validation of reported GLT6D1 (Rs1537415), IL10 (rs6667202), and ANRIL (rs1333048) single nucleotide polymorphisms for aggressive periodontitis in a Brazilian population - Taiete, Tiago; Casati, Marcio Zaffalon; Stolf, Camila Schmidt; Corrêa, Mônica Grazieli; Santamaria, Mauro Pedrine [UNESP]; Andere, Naira Maria Rebelato Bechara [UNESP]; Coletta, Ricardo D.; Sallum, Enilson Antonio; Júnior, Francisco Humberto Nociti; Silvério, Karina Gonzales; Casarin, Renato Corrêa Viana (Wiley, 2019)
Background: Aggressive periodontitis (AgP) is influenced by genetic factors. Recently, the single nucleotide polymorphisms (SNPs) rs1537415 (GLT6D1), rs6667202 (IL10), and rs1333048 (ANRIL) were associated with AgP in different European populations. However, these specific SNPs have not yet been determined in Brazilians. Therefore, this study investigated whether these SNPs previously associated with AgP could be replicated among Brazilians. Methods: The SNPs rs1537415, rs6667202, and rs1333048 were genotyped using 5′-nuclease allelic discrimination assay in AgP (n = 200), chronic periodontitis (CP, n = 190), and healthy patients (H, n = 196). Differences in allele and genotype frequencies were analyzed using chi-square tests and stepwise logistic regression. Results: The minor C allele of rs6667202 was less frequently detected in AgP patients (23.5%) when compared to non-AgP groups (H = 34.2% and CP = 30.3%; p < 0.01), making the SNP protective againstAgP occurrence. Moreover, the final logistic model for AgP diagnosis included gender (p = 0.001) and the SNP rs6667202 (p < 0.001) as significant variables. The SNPs rs1537415 and rs1333048 did not show associations with AgP. Conclusion: Only the SNP rs6667202 was associated with AgP in a Brazilian population, being the minor C allele protective against AgP. Moreover, SNPs rs1333048 and rs1537415, previously associated with AgP in other population, was not validated to Brazilian population.
Keywords: Alleles; Genetic markers; Genetic variation; Genotype; Periodontal diseases